Analisis Nilai Tambah Tape Ubi Jalar Ungu pada Agroindustri Tape 25 Bondowoso - Erika Rifkiyah Rahmatillah; Sulistyaningsih Sulistyaningsih; Gema Iftitah Anugerah Yekti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
In developing agricultural-based businesses, such as agribusiness and agro-industry, the agricultural sector can serve as a basis for the growth of other rural economic activities. Sweet potato purple is an agricultural commodity that is widely processed into products. Purple sweet potato tape is the latest innovation in the Bondowoso area. The resilience of the